Pengaruh Model Pembelajaran Discovery Learning Berbasis Outdoor Learning terhadap Motivasi Belajar Siswa Kelas X SMA Negeri 25 Bone - Nurul Shafira; Sitti Asmah; Erwing Erwing (SENTRI: Jurnal Riset Ilmiah, 2026)
Education is a very important part of a nation, especially a nation that is developing its human resources so that they can follow a more advanced civilization with various technological advances that are increasingly advanced. Education is a place where teachers, who act as the main educators in the classroom, provide knowledge to students to influence changes in behavior, knowledge, and abilities. This study aims to prove the influence of the Outdoor Learning-Based Discovery Learning model on the Learning Motivation of Class X MIPA SMA NEGERI 25 BONE. The research used is quantitative research with the type of Pre-Experimental Design research with the type of One Group Pre-test and Post-test Design. The research sample is class X.1 with a total of 29 students. The data collection techniques used in this study were the provision of Pre and Post questionnaires, student learning motivation, and documentation. According to the data analysis that has been carried out using SPSS (Statistical Package for the Social Science) for windows 23 as a data management tool which shows that the normality test on the Shapiro-Wilk results shows that the Pretest (sig) values > (0.05) or (0.100) > (0.05) and Postest (sig) > (0.05) or (0.093) > (0.05) are normally distributed. After the normality test is carried out, then a homogeneity test is carried out to find out whether the data from the population is homogeneous or not, stating the probability (0.80) > (0.05) so that it can be concluded that the homogeneous population is accepted.